PERAN KOMUNIKASI TERHADAP PENINGKATAN KINERJA ORGANISASI HIMPUNAN MAHASISWA TEKNOLOGI PENDIDIKAN UNIVERSITAS MUHAMMADIYAH MAKASSAR - Irwan Aditia; Muh. Dzuljalali Wal Ikram; Maman A. Majid Binfas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The role of communication in improving the organizational performance of the Education Technology Study Program Student Association at Muhammadiyah University of Makassar is the subject of this research. The method used is qualitative with a descriptive approach. Effective communication, both vertical and horizontal, significantly affects organizational performance, especially in terms of coordinating activities, resolving conflicts, and achieving organizational goals. The results showed that effective communication, both vertically (between leaders and members) and horizontally (between fields and among members), had a significant effect on organizational performance. Open and participatory communication encourages more efficient coordination of activities, minimizes internal conflicts, and accelerates the achievement of common goals.